Perlindungan Hukum terhadap Pelaku Ekonomi; Relevansi Pasal 8 The Universal Declaration of Human Rights dan Hukum Islam - Muhammad Ilham Pratama; Tajul Arifin; Ine Fauziah (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the relevance between Article 8 of the Universal Declaration of Human Rights (UDHR) and the principles of Islamic law in ensuring legal protection for economic actors, as well as to identify points of convergence that can strengthen the national economic legal system to make it more just and humanistic. This article is categorized as library research using a qualitative approach. The methodology applied is a normative-juridical study. Primary data were obtained from the official texts of the UDHR, the Qur’an, Hadith, and literature on fiqh muamalah, while secondary data were derived from books, scholarly journals, and relevant legislation. The findings indicate a substantial alignment between the principle of effective remedy in Article 8 of the UDHR and the values of justice in Islamic law. Both emphasize the state’s responsibility to ensure effective, transparent, and equitable legal protection for every economic actor. Therefore, harmonizing international human rights norms with Islamic law becomes an essential step in realizing a legal protection system that is not merely legalistic but also grounded in universal morality and humanity.